Formulation and evaluation of mucoadhesive microspheres of cimetidine - SK. Arifa Begum; D. Basava Raju (International Journal of Pharmacy and Analytical Research, 2020)
The intention of the present study is to formulate mucoadhesive microspheres containing cimetidine by employing xanthan gum & gum kondagogu as mucoadhesive agent and by adapting ionotropic gelation technique. Response Surface Composite design was employed to study the effect of independent variables, polymer concentration (X1) and sodium alginate concentration (X2) on dependent variables mucoadhesion time. The best batch exhibited a high drug entrapment efficiency of 97.12% and a swelling index of 96.98%; percentage mucoadhesion after 10 h was 98%. The drug release was also sustained for 12 h. The prepared mucoadhesive microspheres were characterized for various properties like preformulation, flow properties, in vitro mucoadhesion, in vitro drug release, entrapment efficiency and surface properties. The external and internal surface morphological characteristics of mucoadhesive microspheres were investigated using Scanning Electron Microscope (SEM). The formulation which showed better flow properties, in vitro drug release and entrapment efficiency was selected as optimized formulation i.e., formulation MGK5. The in vitro release profiles from optimized formulations were applied on various release kinetic models of drug and suggested that the drug release from microspheres followed non-fickian diffusion. The optimized formulations MGK5 was subjected to stability studies for six months at 400 ±20C & 75±5%RH as per ICH guidelines and result showed that there were no changes in physical parameters, formulation parameters and in vitro release studies.